PRAKTIK PAKATAN DALAM PENYELENGGARAAN WALIMATUL URSY DI DESA SEKUDUK KECAMATAN SEJANGKUNG KABUPATEN SAMBAS PERSPEKTIF HUKUM EKONOMI SYARIAH - Yuni Saputri; Marluwi Marluwi; Nanda Himmatul Ulya (Al-Aqad, 2024)
The purpose of this research is to find out the practice of pakatan in organizing walimatul ursy in Sekuduk Village, Sejangkung Sub-district, Sambas Regency and the results of sharia economic law review on this pakatan practice. This type of research is field research. The research used interview techniques. Primary data sources were obtained directly from informant interviews, while secondary data sources were obtained from literacy references. Data validity checking techniques used are source tringulation and technique tringulation. The results of this study indicate that the implementation of pakatan on walimatul ursy is done by the way the recipient of the pakatan comes directly to the pakatan recipient's house by bringing goods in the form of consumer goods for organizing walimatul ursy. Then, in the next pakatan the recipient must return the goods of the other pakatan participants, at the time of the walimatul ursy at a later time as previously given according to the same number of items. In terms of Sharia Economic Law, the practice of pakatan is associated with debt and credit/al-qard. Judging from the pillars and conditions of debt and credit/al-qard, namely the existence of a debtor and also the existence of a debtor, and a clear object in debt and credit/al-qard, and strengthened by a contract by meeting directly between the two parties.